Microwave non-destructive testing of coatings and paints using free space microwave measurement / Norhayati Hamzah ... [et al.] - Hamzah, Norhayati; Ghodgaonkar, Deepak Kumar; Che Kasim, Kamal Faizin; Awang, Zaiki (Institute of Research, Development and Commercialisation (IRDC), 2005)
Microwave nondestructive testing (MNDT) techniques are applied to evaluate quality of anti-corrosive protective coatings and paints on metal surfaces. A tree-space microwave measurement (FSMM) system is used for MNDT of protective coatings. The FSMM system consists of transmit and receive spotfocusing horn lens antennas, a vector network analyzer, mode transitions and a computer. Diffraction effects at the edges of the sample are minimized by using spot-focusing horn lens antennas. Errors due to multiple reflections between antennas are corrected by using free-space LRL (line, reflect, line) calibration technique. We have measured complex reflection coefficient of polyurethane based paint which is coated on brass plates.